The effect of Coriandrum sativum L. on yogurt: a comprehensive study of physicochemical, microbiological, sensory, and textural properties - Turgut, Tamer; Diler, Abdulkerim (Frontiers in Nutrition, 2025)
ObjectivesThe objective of this study was to investigate the effects of the addition of Coriandrum sativum L. (coriander) on the physicochemical, sensory, textural and microbiological properties of yogurt.MethodsTo conduct this study, 4 types of yogurt were prepared as control (C0) and with 1% (C1), 2% (C2) and 3% (C3) coriander, and the yogurts were analyzed on specific storage days.ResultsThe addition of coriander significantly influenced some physiochemical parameters (syneresis, titratable acidity) of yogurts (p < 0.05). The storage time significantly affected the water holding capacity (WHC), syneresis and titratable acidity (TA). The TA of the yogurts increased during storage. The addition of coriander significantly influenced the color parameters (ΔE, C* and YI) of yogurts (p < 0.05). The results of the statistical analysis indicated that storage time had a significant effect on the viability of yogurt bacteria (p < 0.05). While the number of Lactobacillus bulgaricus decreased, an increase was observed in the number of Streptococcus thermophilus. The number of both yogurt bacteria remained above 7.46 log cfu/g throughout storage. The addition of coriander to yogurt led to changes in the number of yogurt bacteria. When the texture parameters of the yogurts were compared, no significant difference was seen between the yogurts. The sensory evaluation showed that yogurts with coriander had a higher overall acceptability than C0 yogurts.ConclusionThe results of the research indicate that the addition of coriander has a positive effect on the quality of yogurt. The results of this study suggest that the inclusion of coriander and other similar aromatic plants in yogurt production could be beneficial in terms of producing functional yogurt and the potential uses of these plants should be investigated.